Wasiat Dalam Tinjauan Hukum Islam Dan Hukum Adat - ahsin, moh (Al-Inṣāf, 2022)
This article aims to answer questions about: 1) Is there a difference between testamentary law in Islamic law and customary law?, 2) When will the will be carried out in a review of Islamic law and customary law?, 3) Can a will be withdrawn and when will a testamentary gift be deemed invalid ?. The law of origin rather than a sunnah testament, and sometimes it also becomes mandatory, permissible, makruh, unlawful according to the qarinah that affects it. In general, testamentary grants can be withdrawn either according to Islamic law, custom or BW. This is in line with the nature of a testamentary grant which is a final will. So if the bequest is withdrawn by the donor, it is clear that this is not his last wish. In the legal environment of Islamic law, custom, BW) the withdrawal of the inheritance grant can be carried out in two ways: openly (uitdurkkelijk) and secretly (Stilzwijgend) Keywords: Wills, Islamic Law, HKI, Customary Law